Critical Race and Religion: Unpacking Whiteness and Decolonizing the Study of Religion - Nye, Malory (Implicit religion, 2022)
Laura McTighe (2020, 299) argues in the Journal of the American Academy of Religion that "Religious Studies has a race problem." I strongly agree with this argument: not only does the field largely ignore issues of race in its examination of cultural and religious differences, but also the field itself was formed and developed (largely over the nineteenth and twentieth centuries) in the context of British, continental European, and American colonialism. That is, the field of religious studies has in particular a whiteness problem. In short, the study of religion has the issue of race and racialization at its centre—and thus any attempt to explore issues of critical religion should also embrace critical race theory in all its forms. Drawing on writers such as Sara Ahmed, Aime Cesaire, Angela Y Davis, W.E.B. Du Bois, and Toni Morrison, I will examine some of the contours of what a "Critical Race and Religion" approach may contribute to a decolonized study of religion—including a strong critique of the underlying issues of whiteness (and white supremacy) within the contemporary field.